A FEW DIFFICULTIES WITH DICTIONARY ENTRIES’ STRUCTURATION - Usmonov , Asliddin (Educational Research in Universal Sciences, 2023)
In this article, I will discuss the importance of dictionaries for language learning. Since regional dictionaries are a source of confusion, it is evident how important it is to study them. Additionally, it is crucial to look into the semantic changes in the English language’s meaning system in order to provide a quantitative and qualitative growth of the language’s expressive resources.